The haplotype-resolved telomere-to-telomere genome and OMICS analyses reveal genetic responses to tapping in rubber tree - Chaochao Li; Yuan Yuan; Zhiyi Nie; Tingkai Wu; Zhiyuan Wang; Jiangxia Qiao; Zhi Deng; Xiaobo Wang; Dong Xu; Xu Wang; Shuo Cao; Bingqin Li; et al. (Nature Communications)
Abstract Rubber tree (Hevea brasiliensis) is the primary source of natural rubber and economically important. We present the haplotype-resolved, telomere-to-telomere, gap-free genome assembly of the cultivar CATAS 7-33–97, with both haplotypes containing complete telomeric and centromeric regions. Structural variations, including a 32.71 Mb inversion on chromosome 8, are identified. The fully assembled 36 chromosomes enable comprehensive identification of rubber biosynthesis genes and their allele-specific expression. By integrating transcriptomic and metabolomic data, we reconstruct the rubber biosynthesis pathway and confirm the mevalonate (MVA) pathway as the major carbon source for rapid latex regeneration during tapping. Jasmonic acid (JA) plays a key role in promoting rubber yield by enhancing biosynthetic activity in response to mechanical wounding. We propose a model where JA-induced myelocytomatosis proteins 2 activate mevalonate kinase 1 expression, boosting MVA synthesis and rubber production. These findings provide insights into rubber tree genomics and its molecular response to tapping.